Between sectionalism and revitalisation: Trade unions and activation policies in Europe - Clegg, Daniel; Graziano, Paolo; van Wijnbergen, Christa (The University of Edinburgh, 2010)
Though the response of trade unions to activation policies seems a crucial test of their capacity to adapt to the challenges of post-industrialisation, the issue has to date received little systematic attention in the welfare state or labour market policy literature. This paper takes a first step in remedying this curious neglect. Drawing on relevant theoretical literature it first briefly outlines two very contrasting perspectives on how unions’ broad adaptation strategies could be expected to shape their attitude to activation reforms. It then analyses the role played by unions across around twenty years of labour market policy reforms in three strategically selected national case studies, confronting the differing assumptions to some preliminary empirical evidence. The cross-case evidence suggests that union attitudes to activation policies are rarely unambiguous reflections of either pure sectionalism or planned revitalisation platforms, but are instead shaped by a mix of strategic policy trade-offs, institutional incentives as well, at times, by the influence of new policy ideas.
Part of the Working Papers on the Reconciliation of Work and Welfare in Europe series
Keywords: Social Policy